The Role of Financial Literacy and Internalization of Siri' Cultural Values in Improving Family Financial Management of Housewives in Sidenreng Rappang Regency - Haeril, Haeril; Salida, Amrizal; Fadlina, Fadlina; Usman, Usman; Jumadi, Sri Wahyuni (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the relationship between financial literacy, the internalization of Siri' cultural values, and family financial management in Sidenreng Rappang Regency. The research employed is mixed design methods using an exploratory sequential approach, consisting of two phases. The first phase used a qualitative ethnographic approach to describe and understand daily life, social practices, and cultural values within the community by exploring the meaning and practices of the Siri' culture through interviews and observations. The findings were analyzed using Spradley's model, which includes domain, taxonomic, componential, and cultural theme analysis to formulate indicators and develop the measurement instruments for the variable. Meanwhile, the instruments for the other variables were adopted from previous studies. In the second phase, the developed questionnaire was distributed and analyzed using an explanatory-descriptive quantitative approach to explain and describe the relationships between variables. The qualitative findings show that the Siri' culture in Bugis society is not only understood as a sense of shame but also encompasses dignity, honor, and moral integrity. Siri' serves as a social guideline that influences various aspects of life, including economic behavior in this study, specifically family financial management. Our findings reveal that Siri' values can play a positive role in encouraging fruitfulness, financial responsibility, transparency between spouses, and discipline in paying debts. The indicators derived from the qualitative analysis consist of five dimensions: Aja Ripakkasiri' (Do not let yourself be disgraced by others), Aja to Sipakkasiri' (Do not disgrace one another), Appunnai Siri' (Possess a sense of shame), De'na Mappakkasiri' (Do not disgrace others), and Matanre Siri' (Uphold dignity and honor). These were then used as indicators of the Siri' cultural value internalization variable in the quantitative measurement. In the quantitative phase, the results show that financial literacy (X1) and the internalization of Siri' cultural values (X2) have a positive and significant effect on family financial management (Y), both partially and simultaneously. Together, the two independent variables in this study explain 93% of the variation in Family Financial Management.